Responsibility of International Financial Institutions of harmful economic consequences arsing from their development interventions - Barakat, Reham Galal (AUC Knowledge Fountain, 2019)
In recent decades, International Financial Institutions (IFIs) have been strongly criticized for funding a series of harmful projects which led to adverse environmental, social, and economic impacts on borrower countries, such as deforestation, displacement of indigenous peoples, and unemployment. The most notable example of the harmful environmental and social consequences resulting from an IFI funded-project was demonstrated in the Sardar Sarovar dam on the Narmada River in western India, funded by the International Bank for Reconstruction and Development (IBRD) in 1985, which led to the displacement of thousands of farmers and the loss of their livelihood. While examples of the harmful economic impacts resulting from IFIs’ interventions could be found in the Structural Adjustment (SA) programs extended by the International Monetary Fund (IMF) and the IBRD to developing countries. While the role of IFIs has expanded over time, affecting billions of people, their accountability mechanisms remained behind and have been criticized for lacking sufficient independency and enforceability. Moreover, such mechanisms are only concerned with the environmental and social impacts, while the issue of economic accountability has not received due attention by most of IFIs. Though IFIs heavily influence the economic policies of their borrower countries through their structural adjustment programs, they refuse to share the responsibility for the failure of such policies. This paper advocates for holding IFIs legally responsible for the harmful economic consequences arising from their development interventions. The paper identifies the applicable laws and relevant primary rules from which the international obligations of IFIs are derived and discusses the human rights obligations under international law and the extent of its applicability to IFIs. Then, the paper applies the rules of the responsibility of IFIs on the case of the IMF interventions in Argentina. Finally, the paper identifies the appropriate dispute settlement mechanisms to which states and non-state actors could raise their claims against IFIs.